Root Map of Risk, Perception and Action at Retail Traders of Honey Watermelon - Andreas, Angga; Badrudin, Redy; Nusril; Behera, Sonali (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
The front side of the coin represents business potential, while the reverse side depicts the associated business hazards, indicating that risk is an important component of enterprise. The root cause of the risk, which can be used to decide what action to take, can be difficult to identify, when the hazard is not clearly characterized, as this may result in action simply covering the risk. Similar concerns exist in the honey watermelon business. This study involved 28 fruit traders (retailers) who were selected based on the census method. This research has three objectives. First, find out the root cause (risk) of the honey water melon trade to fruit traders in Bengkulu City by using the Ishikawa diagram analysis tool (risk causal map analysis). The research results obtained are prejudiced. Second, to find out the perceptions of fruit traders on the risks of the honey watermelon trade in Bengkulu City using the Likert-scale-analysis tool, the results are 75% categorized as neutral. Third, to find out the actions of the trader group on the risk of buying and selling honey melon. iIt is mostly carried out in Bengkulu City using a qualitative descriptive analysis tool, and the research results obtained by the traders choose to do research (examine) and carry out risk identification.